Antioxidant Properties of Some Traditional Iranian Edible Fruits Growing Wild in Lorestan Province in the Western Iran - Ebrahim Falahi; Hassan Ahmadvand; Esfandiar Hasani Moghadam; Sajjad Roosta * (Lorestan University of Medical Sciences, 2020)
Background and Aim: This study aimed to determine the antioxidant properties of Ziziphus nummularia (ZN), Crataegus spp (CS) (red), Crataegus spp (CS) (yellow), and Berberis integerrima (BI) which grow in the Western Iran. Materials and Methods: The free radical scavenging ability, total antioxidant capacity, and phenol as well as flavonoid contents were measured using the 2, 2 diphenyl-1-picrylhdrazyl (DPPH), phosphomolybdate, Folin-Ciocalteu, and Zishen methods, respectively. Results: The total antioxidant capacities of ZN, CS (red), CS (yellow), and BI were 0.93±1.15, 1.01±1.14, 1.42±3, and 3.36±4.84 (µmol ascorbic acid/gram of dry extract), respectively. The total flavonoid contents of ZN, CS (red), CS (yellow), and BI were 0.46±0.14, 0.98±0.17, 1.25±0.12, and 3.55±1.80 (mg quercetin/gram of dry extract), respectively. The total phenol content of the extracts ranged from 255.96±78.17 (ZN) to 5128.04±501.61 (CS yellow) mg of gallic acid/gram of dry extract. The lowest IC50 value (3892.25±1298.51 µg/ml of extract) was observed in CS (yellow) and the highest case (5571.35±31.06 µg/ ml) belonged to CS (red). Conclusion: The results of the present study indicated that all the samples were rich in phenolic and flavonoid contents.